Healing of ExcisionAl wounds on Lower legs by Secondary intention (HEALS) cohort study. Part 1: a multicentre prospective observational cohort study in patients without planned compression. (1st October 2022) - Pynn, Emma V.; Ransom, Myka; Walker, Benjamin; McGinnis, Elizabeth; Brown, Sarah; Gilberts, Rachael; Trehan, Pooja; Jayasekera, Prativa S. A.; Veitch, David; Hussain, Walayat; Collins, Jemma; Abbott, Rachel Angharad; et al.
Abstract: Background: There is no agreed treatment pathway following excision of keratinocyte cancer (KC). Compression therapy is considered beneficial for secondary intention healing on the lower leg; however, there is a lack of supportive evidence. To plan a randomized controlled trial (RCT), suitable data are needed. We report a multicentre prospective observational cohort study in this patient population with the intention of informing a future trial design. Aim: To estimate the time to healing in wounds healing by secondary intention without planned postoperative compression, following excision of KC on the lower leg; to characterize the patient population, including factors affecting healing; and to assess the incidence of complications. Methods: This was a multicentre prospective observational cohort study. Inclusion criteria were age ≥ 18 years with planned excision of KC on the lower leg and healing by secondary intention, an ankle–brachial pressure index (ABPI) of ≥ 0.8; and written informed consent. Exclusion criteria included planned excision with primary closure, skin graft or flap; compression therapy for another indication; planned compression; inability of patient to receive, comply with or tolerate high compression; or a suspected diagnosis other than KC. Results: This study recruited 58 patients from 9 secondary care dermatology clinics. In the analysis population (n = 53), mean age was 81 years (range 25–97 years), median time to healing was 81 days (95% CI 73–92) and 45 patients (84.9%) had healing of the wound at the 6‐month follow‐up. The healing prognostic factors were wound parameters and ABPI. Wound infections occurred in 16 participants (30.2%). Four patients (7.5%) were admitted to hospital; three because of an infection and one because of a fall. Conclusions: The collected data have informed the RCT preparation. A relatively high proportion (7.5–15%) of unhealed wounds, infection and hospital admissions demonstrate the need for clearly establishing potentially effective treatments to improve outcomes for this population. Abstract : People who have surgical excision of keratinocyte cancer on the lower leg often have wounds left to heal by secondary intention; compression therapy is frequently considered to aid healing but this lacks evidence of effectiveness. This article describes a cohort study designed to provide data needed to design an RCT comparing standard care vs. standard care and compression therapy. Fifty‐eight patients were recruited from secondary care dermatology clinics. Data on population characteristics, time to healing, potential prognostic factors for healing and adverse events are reported.